Pengaruh Seleksi Dan Kompetensi Terhadap Prestasi Kerja Karyawan Pada Pt.Karya Murni Sentosa Padang - Syahril , Syahril (CV. ITTC INDONESIA, 2021)
In a company selection one way to get capable and competent employees in accordance with their work, because the selection problem is an important problem in a company to assess the competence of new employees because if a company has employees who do not have this competence will endanger the company is in its development, because this competence is a basic characteristic of someone who allows it to provide superior work performance in certain jobs, roles or situations, so the selection problem cannot be underestimated in a company, because of the mistakes in making a selection we will not find employees who have competence in their fields, for that selection is very necessary in a company, in conducting the selection there are procedures that must be followed by the human resource development team so as not to run away from the actual concept, Because both of these aling related to each other that must be considered by the leadership of the company, because it will have an impact on employee performance at PT, Karya Murni Sentosa. The problem faced by PT, Karya Murni Sentosa is the low work performance of its employees, because they do not have the competence in accordance with their fields this is caused by errors in employee selection. The selection system that has been carried out so far still uses a closed system even though it has received employees at the job fair, but during the interview it still chooses its relatives. In this study, of the two independent variables studied, both of these variables both partially and simultaneously have a significant effect on employee performance at PT. Karya Murni Sentosa namely selection and competency variables. The population in this study was 18 employees, where all populations were directly sampled using total sampling techniques.